Technique and efficacy of pain control after major breast surgery in Srinagarind Hospital - Vattanasiriporn, Naruemon; Thitinasakul, Kanittha; Wittayapairoj, Aumjit; Intrapongpan, Jedniphat; Poorakorn, Sasiwan; Talsoi, Pantipha; Uma, Bussaba (Journal of Medicine and Health Sciences, 2025)
The incidence of breast cancer has increased over the years, and breast surgery remains the mainstay treatment. Effective acute postoperative pain management has a significant impact on the quality of life. This study aims to evaluate efficacy of pain control management after major breast surgery in Srinagarind hospital. This retrospective descriptive study was approved by the institutional ethics committee; we extracted data from patients who underwent major breast surgery between January 1, 2020, and December 31, 2022. Patients aged over 18 years and ASA physical status of I-III were included. Patients who underwent bilateral breast surgery, breast reconstruction, and incomplete anesthetic records were excluded. Patient demographic data, type of surgeries, anesthetic techniques, postoperative pain scores, cumulative opioid requirements, and opioid-related complications were collected in the study. From this study, 302 out of the 523 patients met the inclusion criteria. All the patients were female, with 53.6% undergoing modified radical mastectomy and 85.4% receiving general anesthesia (GA) alone for surgery. None to mild pain at the Post-Anesthesia Care Unit (PACU) was reported by 51.9% of patients. Combining GA with any regional anesthesia (RA) technique significantly reduces the incidence of severe pain in the PACU. More than 46% of patients who had GA alone reported severe pain, but only 31.8% who had both GA and RA together (p-value=0.036). From this study, over half of the patients undergoing major breast surgery in our hospital experience adequate pain control. The combination of RA with the GA technique improves the acute postoperative pain relief.